Handling of the Preparation of Wicker Raw Materials with ABC Analysis Approach - Kartini, Nuri (Ann Publisher, 2023)
In connection with the importance of ABC method analysis in company management, this can be applied to rattan companies that aim to classify or group raw material inventories and find out the raw material items often used in each production. From the results of this study, it can be concluded that the ABC analysis approach to controlling rattan raw material inventory can be classified as follows: Class A classification is classified as raw materials that require strict control, consisting of Mandola Polished AB rattan raw materials, CL rattan Lasio Mandola Polished BC rattan. Class B classification is classified as requiring moderate control, consisting of 8 items of rattan raw materials, namely Tohiti rattan, which has a percentage of total cost, Subaliyu rattan, Semambo rattan, Pietrit rattan, Mandola Semi Polished AB rattan, Mandola Semi Polished CD rattan, Core rattan, Manau rattan. Class C classification includes loose control, consisting of 4 rattan raw materials items: Mandola Semi Polished BC rattan, Jawit rattan, Mandola Semi Polished CD rattan, and Sanjat rattan.